Analysis of Optical Performance Degradation in an Ion-Doped Liquid-Crystal Cell with Electrical Circuit Modeling - Jeong-Ho Seo; Jae-Won Huh; Ho-Jin Sohn; Eunjung Lim; Tae-Hoon Yoon (Crystals, 2020)
We reported electrical circuit modeling to analyze the optical performance degradation in an ion-doped liquid-crystal (LC) cell, which exhibited advantages, such as excellent optical performance and simple switching process, but suffered from long-term reliability issues. When an electric field was applied to the cell for an extended period of time, the optical performance became nonuniform, and the haze in the opaque state decreased. By measuring the impedance and fitting the measured data by using an equivalent circuit model, we confirmed the changes of the parameters in the electrochemical impedance spectroscopy and electrophysical properties of the ion-doped LC cell with time. According to the measurement of the optical and physical characteristics, the optical performance degradation was caused mainly by the ionic materials.